Achieving rapid internationalization of sub-Saharan African firms: Ethiopian Airlines' operations under challenging conditions - Osama Sam Al-Kwifi (18061030) (2020)
Having expanded their global operations, many African firms have begun to appear on the radar screens of multinational players. The distinctive nature of the African continent has directed these firms to follow unconventional paths to internationalization. This study explores the strategies employed by Ethiopian Airlines to overcome the challenges of its operating environment and to achieve rapid internationalization. These strategies were shaped by the act of leveraging accumulated capabilities to meet regional and global demands. In this context, the implementation of a special management structure was instrumental for supporting effective decision making, guiding airline operations, building effective customer-oriented service, and quickly expanding a global network. Finally, the implications of this research will be used to define successful routes for other African firms. Other Information Published in: Journal of Business Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jbusres.2019.02.027